Strain-specific battery of tests for domains of mania: effects of valproate, lithium and imipramine - Flaisher-Grinberg, Shlomit; Einat, Haim (Frontiers in Psychiatry, 2010)
The lack of efficient animal models for bipolar disorder (BPD), especially for the manic pole, is a major factor hindering the research of its pathophysiology and the development of improved drug treatments. The present study was designed to identify an appropriate mouse strain for modeling some behavioral domains of mania and to evaluate the effects of drugs using this strain. The study compared the behavior of four strains: Black Swiss, C57Bl/6, CBA/J and A/J mice in a battery of tests that included spontaneous activity; sweet solution preference; light/dark box; resident-intruder; forced-swim and amphetamine-induced hyperactivity. Based on the ‘manic-like’ behavior demonstrated by the Black Swiss strain, the study evaluated the effects of the mood stabilizers valproate and lithium and of the antidepressant imipramine in the same tests using this strain. Results indicated that lithium and valproate attenuate the ‘manic-like’ behavior of Black Swiss mice whereas imipramine had no effects. These findings suggest that Black Swiss mice might be a good choice for modeling several domains of mania and distinguishing the effects of drugs on these specific domains. However, the relevance of the behavioral phenotype of Black Swiss mice to the biology of BPD is unknown at this time and future studies will investigate molecular differences between Black Swiss mice and other strains and asess the interaction between strain and mood stabilizing treatment.